PENGARUH EARNING PER SHARE, KEBIJAKAN DIVIDEN, ARUS KAS, LEVERAGE DAN RETURN ON ASSETS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Chandra, Angelin; Putri, Arie Pratania; Angela, Leoni; Puspita, Henny; Auryn, Felicia; Jingga, Faby Clariesta (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
The research was conducted in order to add insight and to find out whether Earning per Share, Dividend Payout Ratio, Cash Flow, Leverage, Return on Assets affect the value of company in property and real estate sector companies listed on Indonesia Stock Exchange for the 2013 – 2017 period. There are 75 companies and 15 sample companies that we obtained from this study using purposive sampling techniques. Descriptive quantitative is used in this type of research. The results showed that Earning Per Share, Dividend Payout Ratio, Debt to Equity Ratio and Return On Assets partially had a positive effect on firm value in property and real estate companies. While Cash Flow has no effect and is not significant.